Test anxiety, emotional regulation and academic performance among medical students: a qualitative study - Nora Alshareef; Sabir Giga; Ian Fletcher (Medical Education Online)
Medical school can be a difficult and emotionally turbulent experience for students. Test anxiety is very common among medical students and may impact their academic performance. However, there is a lack of qualitative studies on test anxiety and emotion regulation in relation to the academic performance of medical students. This study aims to examine the relationship between test anxiety and academic performance among medical students, exploring the role of emotion regulation and coping strategies in managing test anxiety during examinations. The study involved 22 medical students from one Saudi medical school who participated in semi-structured interviews. The interviews were recorded and transcribed verbatim. A thematic analysis was conducted on the transcribed data, resulting in the identification of four key themes. The emerging themes are test anxiety, academic performance, emotion regulation, and other coping strategies. Students’ anxiety can vary from a source of motivation to a severe obstacle. It impacts their theoretical understanding, practical abilities, and the evaluation criteria used to assess academic achievement. However, some students use both adaptive and maladaptive emotion regulation strategies. Promoting emotion regulation and various coping mechanisms to address test anxiety in medical students is essential to enhance their academic performance and prepare them for future healthcare professions.